2021
DOI: 10.3758/s13421-021-01224-8
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking and the cognitive reflection test: Evidence for intuitive correct responding and uncertain heuristic responding

Abstract: The Cognitive Reflection Test (CRT) has been used in thousands of studies across several fields of behavioural research. The CRT has fascinated scholars because it commonly elicits incorrect answers despite most respondents possessing the necessary knowledge to reach the correct answer. Traditional interpretations of CRT performance asserted that correct responding was the result of corrective reasoning involving the inhibition and correction of the incorrect response and incorrect responding was an indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…7. This measure was based on the previously used dwell-based measure in (Purcell et al, 2022) and in line with literature relating dwell-time to the depth with which that information is processed (e.g., Glöckner & Herbold, 2011;Rayner, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7. This measure was based on the previously used dwell-based measure in (Purcell et al, 2022) and in line with literature relating dwell-time to the depth with which that information is processed (e.g., Glöckner & Herbold, 2011;Rayner, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Training blocks differed from test blocks in that participants were only presented with the problem once and without a timing constraint. Participants were given feedback (correct or incorrect), presented with the full question and answer, and given a brief explanation as to why that was the correct solution (Purcell et al, 2021(Purcell et al, , 2022. For items and feedback see https://osf.io/ej3n2/.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that some forms of conflict during reasoning affects reasoner's eye movements; Ball (2014) found that participants took longer examining conflict problems even when they give belief‐based responses in error (Ball, Phillips, Wade, & Quayle, 2006). Purcell, Wastell, Howarth, Roberts, and Sweller (2022) observed that participants made a greater number of eye movements on incorrect conflict responses, compared to control items. That is, even when participants’ behavioral responses were in error, they showed intuitive sensitivity to the logical information.…”
Section: Introductionmentioning
confidence: 99%
“…That is, even when participants’ behavioral responses were in error, they showed intuitive sensitivity to the logical information. Moreover, recent studies reveal that eye movements are negatively related to judgments of confidence (Purcell et al., 2022) and positively related to the engagement of effortful thinking (Purcell, Wastell, & Sweller, 2022). The growing evidence suggesting that metacognitions and conflict have systematic impacts on eye movements is promising for the use of gaze‐based indicators in determining the intuitive impacts of belief–logic conflict.…”
Section: Introductionmentioning
confidence: 99%